Human and the world in the thought of Al-Ghazali From undermining materialism to spiritualism in knowledge )A Study on the Impact of the Sufi Transformation in Late Ghazali Texts( - إبراهيم, حامد; ناصر, خضر (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This paper deals with Al-Ghazali's view of human in his relationship with the world and God, and the theological, mystical and philosophical foundations of this view, as it deals with three axes, The First is Al-Ghazali's conception of the natural world, and how causal links and relationships are formed,The Second the god issues in Al-Ghazali's theory and his cosmological conception of existence, and thirdly the view of Al-Ghazali The spiritual nature of human and the possibilities of his cognitive development in the context of Al-Ghazali's Sufi theory of knowledge and his relationship with man to build his destiny.